Isolation and Characterization of Amylolytic Lactic Acid Bacteria during Growol Fermentation, an Indonesian Traditional Food - Putri, Widya Dwi Rukmi; Haryadi, Haryadi; Marseno, Djagal Wisesa (Jurnal Teknologi Pertanian, 2012)
Amylolytic lactic acid bacteria are a group of bacteria that capable to use starch as the only carbon source. Lactic acid bacteria naturally present in growol (a traditional food from fermented cassava) is an indigeneous bacteria that groww in cassava based media. The aims of this research were to isolate, characterize, and identify lactic acid bacteria during growol fermentation. Two hundred and thirty one colonies of lactic acid bacteria were isolated during 0, 24, 48, 72, 96, and 120 hours cassava fermentation. Sixty three isolates were characterized as gram positive, katalase negative, and non producing gas from glucose, but only thirteen isolates had amylolytic characteristics. Identification showed that all isolates were Lactobacillus genera specifically Lactobacillus plantarum and Lactobacillus rhamnosus. Keywords: growol, sour cassava starch, lactic acid bacteria, amylolytic ability, Lactobacillus